MANAGING THE PROFIT EFFICIENCY OF THE FEDERAL BUDGET OF RUSSIA - Alla Yu. Chalova (Вестник Российского экономического университета имени Г. В. Плеханова)
Profits of the federal budget of Russia act as an important macro-economic indicator, which shows not only the general budget balance of state and possibility to pursue the active budget policy but also indicate business activity in economy, its progressive or recessive type of development. The article analyzes problems of insufficient efficiency of managing profits of the federal budget of the Russian Federation within the period of Russian economy recession. Efficiency of budget profit management was evaluated by indicators designed by the author. Models of managing profits of the federal budget of Russia were built separately for oil and gas and non-oil and gas profits. The forecast of their values was made for three variants of social and economic development. The author gave recommendations aimed at raising the efficiency of managing profits of the federal budget for the long-term prospect.